2013
DOI: 10.5721/eujrs20134623
|View full text |Cite
|
Sign up to set email alerts
|

Collecting in situ remote sensing reflectances of submersed macrophytes to build up a spectral library for lake monitoring

Abstract: To map the aquatic vegetation of Bavarian (Germany) freshwater lakes in a large-scaled and quick way, remote sensing is a helpful tool. For interpretation of the data, a spectral library of different macrophyte and sediment reflectances is under development. Therefore, multi-temporal in situ remote sensing reflectances were sampled from May to October 2011 with hyperspectral RAMSES spectroradiometers. Occurring spectral variations during the growing season could be linked to biometric and phenological data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
(37 reference statements)
1
23
0
Order By: Relevance
“…The effect of sediment quality on macrophyte growth [21][22][23] was beyond the scope of this study, mainly because the same patches were analyzed for both years. A previous study by Wolf et al [13] already demonstrated the phenologic pattern changes within the growing season. However, that study did not link spectral patterns with temperature effects and it did not apply a modeling approach for phenologic and seasonal comparisons.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The effect of sediment quality on macrophyte growth [21][22][23] was beyond the scope of this study, mainly because the same patches were analyzed for both years. A previous study by Wolf et al [13] already demonstrated the phenologic pattern changes within the growing season. However, that study did not link spectral patterns with temperature effects and it did not apply a modeling approach for phenologic and seasonal comparisons.…”
Section: Introductionmentioning
confidence: 89%
“…Remote sensing offers a timeand cost-effective method to support monitoring approaches including those recommended by the WFD. Due to its capability to deliver information at high spatiotemporal resolution, remote sensing methods offer the potential to observe detailed seasonal changes in macrophyte distribution and water quality [11][12][13][14][15][16][17][18][19]. It can complement hitherto in-situ data collection along transects by divers and is suggested for closing the gap between the snapshots of in-situ mappings of the WFD [10,20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations